PENDIDIKAN SEKS UNTUK REMAJA DI KAWASAN SARITEM KOTA BANDUNG - Olih Solihin; Putri Azzahra; Ahmad Junidi; Rachmawati Windyaningrum (Ilmu Komunikasi, FISIP Universitas Pasundan, 2023)
Sex education for adolescents is needed in order to provide a correct understanding of sex. This study aims to analyze sex education by families through an interpersonal communication approach to adolescents in the Saritem area of ​​Bandung city. This research was conducted with a qualitative approach. Data collection techniques with passive participant observation, in-depth interviews, documentation, and literature study. The results of the study show: The implementation of sex education is as follows: 1. The time for delivery of sex education is not certain but only as needed; 2). Seeing the right momentum; 3). Sex education material must be given comprehensively; 4) presented at a young age; 5) packaged in sharing, dialogue; 6), the child is positioned as an interlocutor; 7) without having to wait for events; 8), and adjust to the needs of the child. The role of parents in providing sex education is that of knowledge providers, evaluators, educators, companions, and monitors in sexual matters. Sex education is given according to the needs of the child without having to start with an event. Delivery is delivered by sharing and interaction is established in a warm atmosphere, by getting closer to children can create good social relations. Actions, are expected to obey parents as conveyed in sex education.